A New Species of Terellia (Diptera, Tephritidae) from Morocco - El Harym, Y.; Belqat, B.; Korneyev, V.A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
Terellia ptilostemi sp. n., a previously unknown peculiar species of the genus Terellia Robineau-Desvoidy, 1830 is described based on the holotype and a large series of paratypes reared from Ptilostemon rhiphaeus (Pau & Font Quer) Greuter (Asteraceae: Cardueae) in Tétouan and Chefchaouen provinces of Western Morocco. The new species has the phallus glans typical for the species of Terellia serratulae group but has extremely uncommon wing pattern of four black crossbands, whereas the other species of the group have entirely hyaline of slightly infuscated wings.  Holotype and most paratypes are deposited in the collection of Laboratory of Ecology, Systematic and Conservation of Biodiversity, Department of Biology, Faculty of Sciences, Abdelmalek Essaâdi University, Tétouan, Morocco.